Juvenile Coho Salmon in the Elwha River Estuary Prior to Dam Removal: Seasonal Occupancy, Size Distribution, and Comparison to Nearby Salt Creek. Issue 4 (21st June 2013) - Quinn, Thomas P.; Harris, Nicole; Anne Shaffer, J.; Byrnes, Chris; Crain, Patrick
Abstract: In addition to the downstream migration of smolts in spring, Coho Salmon Oncorhynchus kisutch also enter estuaries throughout the year but especially in the spring as fry and in the fall as parr. The removal of two large dams on the Elwha River, Washington, has increased the area accessible to salmon and is affecting many aspects of the system. For comparison with the postdam period, when the Elwha River estuary will likely expand in size and complexity, monthly sampling was conducted in the estuary during 2007–2011 to determine patterns of Coho Salmon presence and size prior to dam removal; Salt Creek, a nearby undammed stream, was also sampled to allow comparison of fish size and seasonal timing patterns. The spring smolt migration in the Elwha River included a large fraction of unmarked fish (primarily of natural origin) as well as marked fish from the Lower Elwha Klallam Tribe Fish Hatchery. Subyearlings entered both estuaries during much of the year, exhibiting a peak in September. Coho Salmon from the Elwha River (including wild and hatchery‐origin fish) were larger and more heavily represented in the fall relative to the spring smolt migration compared to those from Salt Creek. Future patterns in the Elwha River may include reduced presmolt use of the estuary if the center of distribution is farther upriver, but improved estuarine habitat may make it more suitable for presmolts.